Desenvolvimento de componentes nanométricos para aplicação em células a combustível à base de sólidos estruturados e filmes finos - Cesário, Moises Rômolos (2009)
The present work aims the preparation of filmes of strontium-doped lanthanum manganite (perovskita) yttria-stabilized zirconia (LSM-SDC) films deposited on substrate of YSZ by means of spin coating technique having as principal objective their application to solid oxide fuel cells of intermediate temperature. La0,8Sr0,2MnO3 and Ce0,8Sm0,2O1,9 were obtained by modified Pechini method by use of gelatin which act as polymerization agent. The powders obtained were characterized by Xray fluorescence, X ray diffraction, electronic scanning microscopy and the superficial area by BET method. The results obtained by X-ray fluorescence showed that the route adopted for obtention of powders was effective in the obtention of the compositions with close values to the stoichiometrics. Ethyl cellulose was used as pore-forming agent and mixed with the LSM-SDC powders in weight proportions of 1:24, 2:23 and 1:9. The films were sintered at 1150 °C for 4 h and characterized by X-ray diffraction and scanning electron microscopy technique (SEM) and atomic force. The phases quantification of the precursory powders and of the obtained films was carried through Rietveld method. According with the analysis of SEM, as the content of ethyl cellulose was increased, the pore distribution in films become more uniform and the pore size reduced. The methodology used for the obtention of the films was very efficient, considering a material was obtained with characteristics that were proper to the application as electrolyte/cathode system to solid oxide fuel cells